Information transmission and ownership consolidation in aid programs - Dreher, Axel; Marchesi, Silvia (CESifo working papers, 2013)
This paper explores the role of information transmission in explaining donors ́choice between project aid and budget support. Budget support increases the involvement of recipient governments in the decision-making process and can thus be an example of a "delegation-scheme." Conversely, project aid represents a more "centralized" type of aid. According to the theory, when countries ́local knowledge is more important than donors ́information, recipient countries ́discretion in the choice of policies should be increased (delegation). Conversely, there should be less freedom in designing policies when donors ́information is more relevant (centralization). The empirical analysis confirms that the importance of donors ́private information influences the amount of project aid, while recipients ́local knowledge is positively correlated with the amount of budget support.
Keywords: 1972-2010; Arbeitspapier; Graue Literatur